The role of Advanced Practice Providers in improving primary care capacity: practice perspectives on challenges and opportunities - Marie Shoen; Ben Webel; Jacqueline Britz; Hailee Hoffman; Jennifer Gilbert; Alex H. Krist; E. Marshall Brooks (Frontiers in Medicine, 2026)
Background In Virginia and across the United States, primary care workforce shortages limit access to care and exacerbate adverse health outcomes. We conducted a statewide survey of primary care practices in 2022 and found that 42% of practices reported losing a physician or Advanced Practice Provider (APP), including Nurse Practitioners (NPs) and Physician Assistants (PAs), in the past year. Adding APPs to primary care teams is one strategy practices are using to mitigate the shrinking availability of primary care physicians. However, APPs face workforce challenges that increase their susceptibility to turnover. Methods Thirteen semi-structured interviews were conducted with fourteen physicians, managers, and administrators within primary care practices in Virginia Health Professional Shortage Areas (HPSAs) that reported losing a clinician in the past year. Participants were asked about experiences with turnover, impacts of turnover, and retention strategies. The role of APPs emerged as a prominent topic across ten interviews. The ten interviews containing discussions around APPs were transcribed and thematically analyzed for this study. Results According to practice representatives, APPs increased primary care capacity at an efficient cost, but practices frequently struggled with APP retention. Participants described numerous reasons for APP departures, including changing specialties, relocating, and seeking higher pay. Turnover was reportedly more common among APPs with limited primary care experience and repeatedly attributed to perceived discomfort with patient complexity or volume. In contrast, some cited a lack of autonomy as a reason for APPs leaving their role. To improve APP retention, participants suggested implementing phased onboarding, intensive mentorship via interprofessional care teams, and ongoing professional development. Conclusions APPs are viewed as a solution to the primary care workforce shortage, but turnover is common and negatively impacts practices and patients. Targeted support could help mitigate some of the obstacles faced by APPs to improve retention. This work was funded by the National Institute of Nursing Research (NINR) Award 75N98023F00078.